2008
DOI: 10.1021/jp710022y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in Pillared Li-Dispersed Boron Carbide Nanotubes

Abstract: Ab initio density-functional theory study suggests that pillared Li-dispersed boron carbide nanotubes is capable of storing hydrogen with a mass density higher than 6.0 weight% and a volumetric density higher than 45 g/L. The boron substitution in carbon nanotube greatly enhances the binding energy of Li atom to the nanotube, and this binding energy (~ 2.7 eV) is greater than the cohesive energy of lithium metal (~1.7 eV), preventing lithium from aggregation (or segregation) at high lithium doping concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 50 publications
5
73
1
Order By: Relevance
“…The small adsorption energies and long distances indicate the three molecules are only adsorbed physically onto the sheet of pristine graphene, which is in good agreement with Leenaerts' study [20]. We should point out that GGA in DFT is not capable of describing physisorption, while local density approximation (LDA) has been shown to be a reliable functional to study systems involving van der Waals interactions [51][52][53] and can give an adsorption energy much closer to the MP2 calculation [54][55][56]. Thus, we also calculated adsorption energies of NO, N 2 O, and NO 2 on perfect graphene through LDA with the Perdew-Wang (PWC) functional [57].…”
Section: Resultssupporting
confidence: 79%
“…The small adsorption energies and long distances indicate the three molecules are only adsorbed physically onto the sheet of pristine graphene, which is in good agreement with Leenaerts' study [20]. We should point out that GGA in DFT is not capable of describing physisorption, while local density approximation (LDA) has been shown to be a reliable functional to study systems involving van der Waals interactions [51][52][53] and can give an adsorption energy much closer to the MP2 calculation [54][55][56]. Thus, we also calculated adsorption energies of NO, N 2 O, and NO 2 on perfect graphene through LDA with the Perdew-Wang (PWC) functional [57].…”
Section: Resultssupporting
confidence: 79%
“…New AM doped pillared carbon materials have been designed to achieve practical reversible hydrogen storage for transportation [10,12,13,32,[40][41][42]. Theoretically, Chen et al discussed the adsorption of H 2 on bare nanotube and Li-doped one, and found that E ad is −0.025 eV and −0.18 eV, respectively [13].…”
Section: Li-doped Single-walled Carbon Nanotubesmentioning
confidence: 99%
“…Carbon nanostructures materials with chemical stability and optimal density, including carbon nanotubes (CNT) [9][10][11][12][13][14], fullerenes [6,15,16], and graphene [10,17], are the most promising hydrogen storage mediums. Among these carbon materials, the properties of the recently discovered graphene represent a quandary.…”
Section: Introductionmentioning
confidence: 99%
“…Materials which are capable of storing hydrogen with high gravimetric and volumetric density, operating under ambient thermodynamic conditions, and exhibiting fast hydrogen sorption kinetics are essential for practical applications. One of the proposed methods for hydrogen storage is to physisorbe hydrogen molecules on light materials with large surface area [3][4][5]. Formerly, many authors have paid attentions on the hydrogen storage property of carbon nanotubes (CNTs) or boron nitrogen nanotubes (BNNTs) duo to the sufficient porous tube structure and large surface area of nanotube [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%